ArterioVenous Malformation within Jejunal Diverticulum: An Unusual Cause of Massive Gastrointestinal Bleeding - Jeffrey K. Lee; John M. Carethers; Pradipta Ghosh (Gastroenterology Research and Practice)
Massive gastrointestinal (GI) bleeding can occur with multiple jejunal diverticulosis. However, significant bleeding in the setting of few diverticulae is very unusual and rare. We report a case of massive gastrointestinal bleeding from an arteriovenous malformation (AVM) within a jejunal diverticulum to underscore the significance of such coexisting pathologies. Mesenteric angiogram was chosen to help identify the source of bleeding and to offer an intervention. Despite endovascular coiling, emergent intestinal resection of the bleeding jejunal segment was warranted to ensure definitive treatment. However several reports have shown jejunal diverticulosis as a rare cause of massive GI bleeding. The coexistence of jejunal diverticulum and AVM is rare and massive bleeding from an acquired Dieulafoy-like AVM within a diverticulum has never previously been described. Awareness of Dieulafoy-like AVM within jejunoileal diverticulosis is useful in preventing delay in treatment.